Influence of different iron levels in nutrient solution on the primary root growth of wheat - Camargo, Carlos Eduardo de Oliveira; de Freitas, José Guilherme; Filho, Antonio Wilson Penteado Ferreira (Pesquisa Agropecuaria Brasileira, 2014)
Seven wheat (Triticum aestivum L.) cultivars were studied regarding Fe toxicity using five different levels of this element (0.56; 5.0; 10.0; 20.0 and 40.0 mg/l) in nutrient solution with aeration, under constant temperature (250 ± 1°C) and pH 4.0. The source of Fe was Fe2(SO4)3, 4H2O. Tolerance was measured by the mean of the primary root length of 20 seedlings grown during 10 days in nutrient solutions with different Fe concentrations. The cultivars BH-1146 and IAC- 17 showed the largest root growth when the concentration of 0.56 mg of Fe3+/l was used in the solution. The cultivar BH-1146 different from the cultivars CNT-8, IAC-5, Alondra-S-46, IAC-24 and Siete Cerros, but did not show significant difference from the cultivar IAC-17. The cultivar IAC-24 presented the shortest roots in this Fe concentration, being significantly different from the other cultivars. As the Fe concentration in the solutions was increased from 0.56 to 40.0 mg/l, reductions in root length were observed according to the degree of tolerance of each cultivar. Cultivars CNT-8 and Siete Cerros were considered tolerant to the increasing levels of Fe in the nutrient solutions, and cultivars IAC-5, IAC-17, Alondra-S-46 and IAC-24 were considered sensitive. The P, K and Ca concentrations decreased in the shoot as the levels of Fe increased in the nutrient solutions. Fe and Mg concentrations in the leaves increased in all cultivars as the levels of Fe increased in the nutrient solution.